How Do Informal Financial Practices Emerge in MSME Management? A Grounded Theory–Informed Thematic Analysis - Iswari, Hanif Rani; Nisful Laili, Choirun; Wandani Mustika Rahma Ba'its Nur, Ayu (Bulletin of Management and Business, 2025)
This study explores how informal financial practices emerge and are sustained in the management of micro, small, and medium enterprises (MSMEs). Departing from conventional financial research that prioritizes rationality and formal accounting systems, this study adopts an inductive perspective that views financial practices as socially constructed, experience-based, and contextually embedded behaviors. Consistent with this approach, the study does not predefine variables but allows conceptual understanding to emerge from empirical evidence. A qualitative design employing grounded theory–informed thematic analysis was used. Data were collected through in-depth interviews, participant observation, and document analysis at Omah Sayur MQ’s, a retail-based MSME in Malang, Indonesia. Data analysis followed iterative stages of open coding, axial coding, and selective coding to identify recurring behavioral patterns, interpretive meanings, and social processes underlying financial management practices. The findings indicate that MSME financial practices are shaped by habitual routines, intuitive judgment, and relational dynamics rather than formal accounting logic. These practices are characterized by reliance on memory, resistance to formal record-keeping, intuition-based financial decision-making, and trust-oriented financial relationships. Integrating these empirical themes, the study inductively constructs Informal Financial Behavior (IFB) as a patterned and context-dependent mode of financial behavior that operates along a continuum of informality rather than as a binary condition. This study contributes theoretically by extending behavioral accounting literature through an empirically grounded conceptualization of informal financial behavior. Methodologically, it demonstrates the relevance of grounded theory for developing behavioral constructs and provides an initial framework for measuring the level of informal financial behavior among MSMEs. Practically, the findings suggest that financial literacy and inclusion initiatives should move beyond technical instruction and engage with existing behavioral patterns to promote more inclusive and context-sensitive financial interventions.